The influence of good governance, professionalism, and work effectiveness on public service quality - Dasuki, Dasuki; Maulidiyah, Vina; Rumefi, Ufi; Syaifudin, Arif (Jurnal Mantik, 2025)
Bangil District, Pasuruan Regency, there are things that need to be discussed related to Good Governance, for example service procedures that are too complicated, there is no certainty of time and price, so public access to services is quite difficult. Such things are elements that will damage the professionalism of employees and agencies because they are examples of poor work effectiveness in an organization and will ultimately affect public services. The method used in this research is a descriptive quantitative method with the help of SPSS version 26, the data collected is questionnaire data totaling 60 respondents.The results of the research conducted show that the variables have a simultaneous influence but only two variables have a significant influence, namely Professionalism and Work Effectiveness in Public Services. Meanwhile, Good Governance partially has an insignificant effect on Public Services.